O trançado da morte nas tramas do tempo: uma leitura da condição feminina em Cartilha do silêncio e A dança dos cabelos. - Brun, André Adriano (2008)
In this research, with base in a perspective analytic-theoretical sociological predominantly, it was aimed to analyze comparatively the relation among time, space and feminine universe, having as focus the representations of the characters' feminine protagonists of the romances pseudomemorialistas Cartilha do silêncio (1997), by Francisco Dantas, and A dança dos cabelos (2001), by Carlos Herculano Lopes. The first chapter, entitled "Time, feminine condition and memory", approach the relation between the feminine protagonists and the time, with emphasis in the categories memory and destiny. The memory is the resource through which the protagonists appeal to explain the force and the inexorability of their tragic destinies. The appeal to her, through the disordered affluence of the memories and images remote or recent, subverts and paralyzes the protagonists' present, appearing for a future without expectations, obscured for the ghosts of the past and for the terrible present condition. The second chapter, whose title is "Space, feminine identity and reclusion", approaches the identity relation among the feminine protagonists and the space in which are inserted. The house, in general, and the room, especially, they are analyzed with base in the speeches in vogue in the focalized times, ruled in the patriarchal moral couple that it promoted, harnessed to a very rigid sexual distinction, a space differentiation of the humankind, linking the man to the external spaces and, the woman, to the interiors. Entitled "Eroticism, violence, madness and death", the third chapter intends to analyze these four elements that, individual and collectively, they identify the five feminine protagonists. These themes, always associated to the feminine nature, they contributed, along the history, to exalt the woman's satanic face. To hide and to subdue this evil facet, it just presented a way to the women: to be dedicated to the marriage and the maternity, undergoing the gear that moved the society. The characters of the referred works try to adjust to this program ideological absolutist, however, be for the violence/oppression to it inherent, be for the simple curiosity, they don't totally submit, sustaining, like this, the two facets the one of the Virgin Mary and the one of the Eva sinner that, in general, they cover great part of the myths concerning the femininity. Be for the faith in the fatality and for the affluence of memories of the past, torturing the present and darkening the characters' future; be for the intimate connection with the same space; be for the shared characteristics and repeated along the generations that succeed; the five protagonists resemble each other and identify, being stagnated in the time and in the space. It is as if them, generation after generation, they had had lessons for the same "spelling book" and they had their destinies interlaced in a same braid, in spite of the distinctions, besides of authors. All - each one to her way - they "dance" in a same rhythm, essentially to circulate, and with few variations according to the choreography.